Implementation of Enhanced Recovery After Surgery (ERAS) for Spine Surgery - Frederick Johan Purnomo (Jurnal Inovasi Global, 2025)
Enhanced Recovery After Surgery (ERAS) is a multimodal protocol applied to perioperative patient care. The ERAS program is implemented by a multidisciplinary, patient-focused team. The application of ERAS in the field of spinal surgery and the literature that discusses it is currently not widely available. The aim of this review article is to discuss the application of ERAS in spine surgery. ERAS in spine surgery has several components ranging from pre-hospital, preoperative, intraoperative, postoperative, post-discharge phases, to continuous activity improvement teams. The methods used include preoperative education and multimodal management of pain and anxiety, multimodal analgesia, blood loss management, the total parenteral nutrition, and early rehabilitation. The ERAS protocol in spine surgery consists of several components that are interconnected with each other. The application of the ERAS protocol to spine surgery focuses on reducing pain, length of stay and morbidity, and reducing the preoperative anxiety.